Application of glyph-based techniques for multivariate engineering visualization. Issue 1 (2nd January 2016) - Glazar, Vladimir; Marunic, Gordana; Percic, Marko; Butkovic, Zlatko
Abstract : This article presents a review of glyph-based techniques for engineering visualization as well as practical application for the multivariate visualization process. Two glyph techniques, Chernoff faces and star glyphs, uncommonly used in engineering practice, are described, applied to the selected data set, run through the chosen optimization methods and user evaluated. As an example of how these techniques function, a set of data for the optimization of a heat exchanger with a microchannel coil is adopted for visualization. The results acquired by the chosen visualization techniques are related to the results of optimization carried out by the response surface method and compared with the results of user evaluation. Based on the data set from engineering research and practice, the advantages and disadvantages of these techniques for engineering visualization are identified and discussed.